Thermally actuated wax valves for paper-fluidic diagnostics. Issue 21 (7th October 2016) - Phillips, Elizabeth A.; Shen, Rui; Zhao, Siyu; Linnes, Jacqueline C.
Abstract : Wax-ink valves can be printed onto paper membranes allowing the controlled stop and start of fluid flow. Each valve can perform multiple actuation steps ( e.g. open–close–open) enabling increased complexity of fluidic operations on paper platforms. Abstract : The complexity of current paper-fluidic diagnostic devices is limited by their imperfect control of reagent incubation and delivery. Valves providing complete fluid obstruction and multiple actuation steps within a single paper-fluidic diagnostic would increase the range of diagnostic bioassays in these porous membranes. Here, we report the rapid fabrication of tunable wax-ink valves that are thermally actuated within porous membranes. Varying width bands of wax-ink were printed onto strips of nitrocellulose and cellulose membranes and characterized by their triggered obstruction and release of fluid wicking through the membranes. To demonstrate the utility of these wax-ink valves, we have transformed a traditional lateral flow immunoassay into a multi-step, semi-autonomous assay that enhances bacterial detection signal intensity 6-fold. The wax-ink valves are applicable to other paper fluidic assays by fully obstructing fluid flow for a sustained reaction time and are able to be actuated multiple times for sequential fluid delivery with minimal user involvement. These easily fabricated wax-ink valves are a versatile addition to the toolkit of fluidic control mechanisms required to develop more sensitive paper-based diagnostics.